COMMUNICATION OF NAD- AND NADP-DEPENDENT DEHYDROGENASE ACTIVITIES IN LYMPHOCYTES WITH OUTCOME OF PREVALENCE PURULENT PERITONITIS - A. A. Savchenko; D. E. Zdzitovetsky; N. A. Luzan (Бюллетень сибирской медицины, 2014)
Aim of this study was to investigate of NAD(P)-dependent dehydrogenases activity in lymphocytes at different outcomes widespread purulent peritonitis(WPP). Enzyme activity in blood lymphocytes was determined by bioluminescent method. Found that patients with a poor outcome of WPP in blood lymphocytes made more pronounced reaction of lipid anabolism and catabolism of xenobiotics. Regardless of the outcome of the disease in blood lymphocytes of WPP patients reduced levels of enzymes activity that determine the intensity of anaerobic and aerobic respiration and the level of plastic processes, but the activation reactions of lipid catabolism and transport products through glycerol-3-phosphate dehydrogenase on reactions of glycolysis. Based on the informativeness of the NAD(P)-dependent dehydrogenases activity in the classification neural network model for the disease outcome, metabolic coefficient is proposed, which has prognostic significance.